The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11832-015-0635-2
|View full text |Cite
|
Sign up to set email alerts
|

Panner's disease: Literature review and treatment recommendations

Abstract: PurposeTo determine the most up-to-date theory on the aetiology of Panner’s disease, to form a consensus on the assessment of radiographs and to evaluate clinical outcome in order to summarise the best available evidence for diagnosis and treatment.MethodsA review of studies to date on Panner’s disease. Studies were eligible if: (1) the study provided criteria for defining Panner’s disease in order to eliminate confounding data on other radiographic entities that were mistakenly grouped and presented as Panner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…4) Claessen et al 3) reported an article reviewing 23 cases of Panner's disease. According to their findings, most cases of Panner's disease were unilateral in distribution and occurred in boys between 6 and 15 years of age and self-limiting disease healing without clinical impairments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Claessen et al 3) reported an article reviewing 23 cases of Panner's disease. According to their findings, most cases of Panner's disease were unilateral in distribution and occurred in boys between 6 and 15 years of age and self-limiting disease healing without clinical impairments.…”
Section: Discussionmentioning
confidence: 99%
“…3) We report on the case of a 5-year-old boy who was younger than the other patients with Panner's disease.…”
mentioning
confidence: 96%
“…Often there is history of trauma or repetitive stress, more specifically valgus stress or increased axial load to the elbow. Valgus stress is probably the most important factor in the pathogenesis of Panner’s disease under the age of five years [ 1 ].…”
Section: Commentmentioning
confidence: 99%
“…Generally the reported outcomes in terms of function and range of motion were good regardless of the treatment. 8 No good comparative studies have shown one method to be superior over another.…”
Section: Articular Osteochondrosismentioning
confidence: 99%